Pemberdayaan kader upaya kesehatan gigi masyarakat (UKGM) untuk pendampingan ibu hamil dalam upaya pencegahan stunting - Munica Rita Hernayanti; Bedjo Santoso; Tri Wiyatini; Sukini Sukini (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2021)
Cadres an important role in stunting prevention. Cadres can be empowered to assist pregnant women in providing education on aspects of nutrition and health. The purpose to increased UKGM cadres in assisting pregnant women and increase the knowledge and attitudes of pregnant women related to nutritional aspects. This community empowered used an approach to UKGM (Community Dental Health Efforts) cadres, in the form of one cadre accompanying one pregnant woman. The service is carried out from March to October 2021 with a target of 50 UKGM cadres and 50 pregnant women in the Gemawang District, Temanggung Regency. Community empowered with one cadre to one pregnant woman approach has been proven to increase the active role of cadres in assisting and providing education to pregnant women, increasing knowledge of pregnant women in nutritional aspects, and increasing cooperation between the Gemawang Health Center and the community.